2017
DOI: 10.1136/bmjopen-2016-014629
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the cerebroprotective effect of inhalation anaesthesia and total intravenous anaesthesia in patients undergoing cardiac surgery with cardiopulmonary bypass: a systematic review and meta-analysis

Abstract: ObjectiveNeurological dysfunction remains a devastating postoperative complication in patients undergoing cardiac surgery with cardiopulmonary bypass (CPB), and previous studies have shown that inhalation anaesthesia and total intravenous anaesthesia (TIVA) may produce different degrees of cerebral protection in these patients. Therefore, we conducted a systematic literature review and meta-analysis to compare the neuroprotective effects of inhalation anaesthesia and TIVA.DesignSearching in PubMed, EMBASE, Sci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 40 publications
0
32
0
Order By: Relevance
“…Ketamine administration during anesthesia induction is related to a lower rate of postoperative delirium and POCD incidence, probably because of the anti-inflammatory effect of the drug (class-2 evidence) [83]. However, a higher POCD incidence was observed after cardiac surgery managed with propofol compared to that with sevoflurane, regardless of the anti-inflammatory effect of propofol [12,84]. Kanbak et al demonstrated greater postoperative cognitive functions following anesthesia maintained with isoflurane than that maintained with sevoflurane and desflurane [85].…”
Section: Anesthesia-related Risk Factorsmentioning
confidence: 99%
“…Ketamine administration during anesthesia induction is related to a lower rate of postoperative delirium and POCD incidence, probably because of the anti-inflammatory effect of the drug (class-2 evidence) [83]. However, a higher POCD incidence was observed after cardiac surgery managed with propofol compared to that with sevoflurane, regardless of the anti-inflammatory effect of propofol [12,84]. Kanbak et al demonstrated greater postoperative cognitive functions following anesthesia maintained with isoflurane than that maintained with sevoflurane and desflurane [85].…”
Section: Anesthesia-related Risk Factorsmentioning
confidence: 99%
“…TIVA may also improve surgical conditions, with reduced blood loss in facial surgery 4 , and allows more effective visual evoked potential monitoring during spinal surgery 5 . In contrast, inhalational anaesthesia may offer other advantages, including ease of use for induction in paediatric patients, and improved cerebral and cardiac protection 6 and reduced postoperative pulmonary complications and mortality following cardiac surgery 7,8 .…”
mentioning
confidence: 99%
“…However, Radtke et al (52) found that the BIS guided anaesthesia decreased the risk of POD, but not POCD. Chen et al (53) also found that the use of inhaled versus total intravenous anaesthetics for cardiac surgery produced higher postoperative scores on the mini mental state exam. Apart from anaesthetics, it is appropriate to try and control other potential pathophysiological causes.…”
Section: Prevention and Improving Outcomesmentioning
confidence: 96%